2017
DOI: 10.1002/lt.24813
|View full text |Cite
|
Sign up to set email alerts
|

National assessment of early hospitalization after liver transplantation: Risk factors and association with patient survival

Abstract: Hospitalization is known to occur frequently in the first 6 months following liver transplantation (LT). Using a novel data linkage between the Scientific Registry of Transplant Recipients and Centers for Medicare and Medicaid Services, our study has two objectives: (i) determine risk factors for “early” hospitalization (i.e., within 6 months of LT) (ii) quantify the importance of hospitalization history in the first 6 months with respect to subsequent patient survival (i.e., survival, conditional on surviving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Our study found that diabetes mellitus impacted the rate ratio of early hospitalization after SLKT as seen in LT‐alone patients. [ 10 ] Although we did not capture the degree of diabetes mellitus control with our study, it is plausible that a lack of glycemic control can increase the risk of early hospitalization given its impact on wound healing and infection risk.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our study found that diabetes mellitus impacted the rate ratio of early hospitalization after SLKT as seen in LT‐alone patients. [ 10 ] Although we did not capture the degree of diabetes mellitus control with our study, it is plausible that a lack of glycemic control can increase the risk of early hospitalization given its impact on wound healing and infection risk.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find any sex‐based differences in early hospitalization rates. Similar to LT recipients, [ 10 ] younger age was associated with an increased incidence rate ratio. We could not find any inflection point for the age.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations